1967
DOI: 10.1002/cjce.5450450608
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of catalytic oxidation of methane: Application of initial rate technique for mechanism determination

Abstract: A kinetic investigation on the oxidation of methane using a palladium catalyst was conducted. Conversions of methane were small and limited to about 10% to facilitate the use of initial rate approach. Plots of initial rate against total pressure and varying feed composition were used to interpret the data qualitatively. Regression coefficients from linearized rate equations and criteria of best fit were used to arrive at a plausible mechanism. The experimental results indicated that the reaction rate is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The partial pressures of the reactants have a crucial impact [35][36][37]. The inhibiting effect of carbon dioxide becomes more visible, when partial pressure of methane is comparably low.…”
Section: Influence Of Carbon Dioxidementioning
confidence: 98%
“…The partial pressures of the reactants have a crucial impact [35][36][37]. The inhibiting effect of carbon dioxide becomes more visible, when partial pressure of methane is comparably low.…”
Section: Influence Of Carbon Dioxidementioning
confidence: 98%
“…The oxidation of methane over supported Pd catalysts has been widely investigated. The study of support effects (Cullis et al, 1972; Cullis and Willat, 1983), catalyst deactivation mechanism (Cullis and Nevell, 1976), reaction mechanism (Mezaki and Watson, 1966; Seimanides and Stoukides, 1986; Cullis et al, 1971; Ahuja and Mathur, 1967), kinetics (Cullis et aL, 1971), and structure sensitivity effects (Hicks et al, 1990a,b) has attracted attention. It has been shown that the order of the reaction with respect to oxygen and methane is 0 and 0.5, respectively (Cullis et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…A simple irreversible catalytic reaction, A->B, whose kinetics is expressed by the following form rA =kKpA0XA/(l +KpA0XAf (1) is assumed to take place in a fluidized bed reactor.…”
Section: Discussionmentioning
confidence: 99%